AN ANALYSIS OF CONSUMER PERCEPTIONS TOWARDS AYURVEDIC PRODUCTS IN MUMBAI (International Journal of Food and Nutritional Sciences, 2022)
Ayurvedic products are traditional medicines derived from natural sources that have been used for centuries in India and other countries. The consumer perception of Ayurvedic products is influenced by various factors such as awareness, beliefs, attitudes, preferences, satisfaction, and loyalty. This paper aims to review the existing literature on consumer perception of ayurvedic products and identify the key drivers and challenges for their adoption and consumption. The paper also suggests some implications for marketers and policymakers to enhance the consumer perception and acceptance of Ayurvedic products.